Understanding the roles of deformation-induced martensite of 304 stainless steel in different stages of cavitation erosion. (March 2021) - Zhang, L.M.; Li, Z.X.; Hu, J.X.; Ma, A.L.; Zhang, S.; Daniel, E.F.; Umoh, A.J.; Hu, H.X.; Zheng, Y.G.
Abstract: In this work, the effect of plastic deformation-induced martensite on the CE behavior of 304 SS was investigated by micro-area XRD, nano indentation and EBSD. Results indicated that the martensitic content initially displayed an increased trend and then decreased in the later stage. The formation of martensite was beneficial to the CE resistance of 304 SS in incubation and rising periods since the impact energy dissipation through martensitic transformation and the strengthening effect of martensite were dominant. However, it was no longer conductive to the CE resistance in stable period in virtue of the severely damaged surface and the markedly reduced plastic deformation ability. In addition, obvious grain refinement was observed in the CE surface layer, which should be correlated with the deformation twins cutting the original grains. Highlights: The deformation-induced martensite in 304 SS plays different roles in CE process. The martensite contents with different CE time are calculated semi-quantitatively. Martensite has markedly strengthening effect promoting CE resistance. Martensite can also reduce the plastic deformation ability reducing CE resistance. CE causes obvious grain refinement in the surface layer of 304 SS.